Reliability and Validity of Prototype Diagnosis for Adolescent Psychopathology. Issue 4 (April 2016) - Haggerty, Greg; Zodan, Jennifer; Mehra, Ashwin; Zubair, Ayyan; Ghosh, Krishnendu; Siefert, Caleb J.; Sinclair, Samuel J.; DeFife, Jared
Abstract : Abstract: The current study investigated the interrater reliability and validity of prototype ratings of 5 common adolescent psychiatric disorders: attention-deficit/hyperactivity disorder, conduct disorder, major depressive disorder, generalized anxiety disorder, and posttraumatic stress disorder. One hundred fifty-seven adolescent inpatient participants consented to participate in this study. We compared ratings from 2 inpatient clinicians, blinded to each other's ratings and patient measures, after their separate initial diagnostic interview to assess interrater reliability. Prototype ratings completed by clinicians after their initial diagnostic interview with adolescent inpatients and outpatients were compared with patient-reported behavior problems and parents' report of their child's behavioral problems. Prototype ratings demonstrated good interrater reliability. Clinicians' prototype ratings showed predicted relationships with patient-reported behavior problems and parent-reported behavior problems. Prototype matching seems to be a possible alternative for psychiatric diagnosis. Prototype ratings showed good interrater reliability based on clinicians unique experiences with the patient (as opposed to video-/audio-recorded material) with no training.